Accumulation and implications of cadmium, cobalt and manganese in soils and vegetables irrigated with city effluent - Murtaza, G.; Ghafoor, A.; Qadir, Manzoor (2008)
BACKGROUND: In most parts of Pakistan, untreated city effluent is utilised for growing vegetables around large urban settlements such as Faisalabad. Farmers use it as a source of irrigation water and plant nutrients. However, its continuous use may have serious environmental implications, since it also contains heavy metals. In this study the Faisalabad city effluent was examined for irrigation quality and its impact on irrigated soils and vgetables. RESULTS: Irrigation hazard of the effluent was moderate (electrical conductivity (EC) 1.1-1.7 dS m-1, Sodium adsorption ratio (SAR) 5.9-17.4mmol1/2 L-1/2, Residual sodium carbonate (RSC) 1.0-2.1mmolc L-1) at site 1 and strong (EC 3.7-4.1 dS m-1, SAR 16.1-21.8mmol1/2 L-1/2, RSC 4.0-9.1mmolc L-1) at site 2.Mean concentrations of ammonium bicarbonate/diethylene triamine pentaacetic acid (AB/DTPA)-extractable Cd, Co andMn at upper soil depth (0.0-0.2m)were respectively 0.080, 0.057 and 217.4mg kg-1 at site 1 and 0.101, 0.076 and 164.1mg kg-1 at site 2. CONCLUSION: The concentrations of Cd and Mn were above the permissible limits but that of Co was below the permissible limit for irrigation. The concentrations of Cd, Co and Mn tended to decrease with increasing soil depth. Accumulation of metals was higher in leaves irrespective of whether leaves were the edible or non-edible component of shoots. Use of untreated city effluent for irrigation without risk assessment and management could be a serious hazard, impacting soil and crop quality and ultimately human health.